10(v+1)-2v=4(2v+4)-17

Simple and best practice solution for 10(v+1)-2v=4(2v+4)-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(v+1)-2v=4(2v+4)-17 equation:


Simplifying
10(v + 1) + -2v = 4(2v + 4) + -17

Reorder the terms:
10(1 + v) + -2v = 4(2v + 4) + -17
(1 * 10 + v * 10) + -2v = 4(2v + 4) + -17
(10 + 10v) + -2v = 4(2v + 4) + -17

Combine like terms: 10v + -2v = 8v
10 + 8v = 4(2v + 4) + -17

Reorder the terms:
10 + 8v = 4(4 + 2v) + -17
10 + 8v = (4 * 4 + 2v * 4) + -17
10 + 8v = (16 + 8v) + -17

Reorder the terms:
10 + 8v = 16 + -17 + 8v

Combine like terms: 16 + -17 = -1
10 + 8v = -1 + 8v

Add '-8v' to each side of the equation.
10 + 8v + -8v = -1 + 8v + -8v

Combine like terms: 8v + -8v = 0
10 + 0 = -1 + 8v + -8v
10 = -1 + 8v + -8v

Combine like terms: 8v + -8v = 0
10 = -1 + 0
10 = -1

Solving
10 = -1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -35=4x-10 | | 220=2.5(50)+b | | (3-w)(3w-1)=0 | | 3-5(n-4)=16 | | 3x+17=22 | | -0.3x+9.13=-0.1x+9.53 | | (2ab+2ab+2ab+2ab+2ab)+(7ab+7ab)+(5ab+5ab)+1ab= | | 3m=5-2m | | cosx=0.4166666667 | | x^2-19x+78=0 | | cosx=.4166666667 | | 5i/4-3i= | | G(2)=3x+5x-2 | | x^4+x^3-14x^2+6x-120= | | (2ab+2ab+2ab+2ab+2ab)(7ab+7ab)+(5ab+5ab)+1ab= | | x=0-3x | | 4+10z-1+5z+59=3z | | C(x)=800+5x^2 | | 4(3x-7)+6=8x-3(2-2x) | | 6[3+2]=15 | | 4(4m-3)=6 | | x=2-3x | | 6x^3+5x^2+x=0 | | 10a+8=4a | | 8=3(-3)+b | | 9x=6x-15 | | solve(3m-2)(9m+5)=0 | | x=-3-3x | | solve(3m-2)(9m-5)=0 | | (7ab+7ab)= | | d/dx=ln(729) | | 100x-0.12=300x+0.88 |

Equations solver categories